Association of plasma microRNA levels with different collateral circulation degree in chronic total occlusion patients with coronary artery disease: a pilot study - A. V. Kiseleva; D. K. Vasilyev; A. G. Soplenkova; F. B. Shukurov; E. A. Sotnikova; D. A. Feshchenko; V. A. Kutsenko; N. A. Arablinsky; O. P. Skirko; A. A. Zharikova; A. I. Ershova; M. S. Pokrovskaya; et al. (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To investigate the association of 10 circulating plasma microRNAs with collateral flow degree in chronic total occlusion (CTO) patients with coronary artery disease (CAD).Materials and methods. Plasma expression levels of 10 circulating miRNAs were measured by real-time PCR using Taqman technology in a sample of 43 subjects. The study included patients with CAD and CTO with good (n=13) or poor (n=10) coronary collateral circulation (CCC) based on Rentrop classification and a control group of patients without significant coronary stenosis (n=20).Results. Significant differences in expression levels were found for 7 circulating miRNAs in patients with CTO and good CCC and for 5 microRNAs in the combined group of patients with CTO compared to the control group. Among the 7 microRNAs, decreased expression of hsa-miR-126-5p, hsa-miR-146a-5p, hsa-miR-155-5p, hsa-miR-15b-5p, hsa-miR-21-5p, hsa-miR-23a-3p and increased expression of hsa-miR-451a were detected. For the first time, we showed that the level of 2 microRNAs (hsa-miR-23a-3p, hsa-miR-21-5p) is significantly reduced and the level of hsa-miR-451a is increased in patients with CAD with good CCC.Conclusion. Plasma microRNAs with significant differences obtained can be used for further studies on a larger sample size as candidate biomarkers for assessing the severity of ССС in the presence of CTO.